THE IMPACT OF ACCOUNTING INFORMATION SYSTEM AS CONTROL AND AUDITORS ON SMES ACCOUNTING PRACTICES - Assistant Professor, Emad Al-Harash (American Journals, 2024)
The influence of accounting information systems (AIS) as control and auditor on the efficacy and efficiency of accounting processes for Iraqi small and medium-sized businesses (SMEs) has not been thoroughly studied. This empirical study is aimed at an analysis made as to how much accounting information systems such as control and auditor may impact SMEs' accounting practices. The AIS of SMEs for measured against standard or prescribed indicators of effectiveness and efficiency for accounting practices. The primary method of measuring the variables was adaption, and it used measures that were created based on earlier research. The outcomes demonstrate that the accounting information system as control and auditor has an immediate positive and significant impact on SMEs' accounting practices. The study adds value to the accounting literature because few works analyse how much an auditor and control’s usage of AIS may affect SMEs' accounting practices in Iraq.
Keywords: Accounting Information System, SMEs, Accounting Practices, Control and Auditor.